Influence of Avocado Purée as a Fat Replacer on Nutritional, Fatty Acid, and Organoleptic Properties of Low-Fat Muffins - Othman, Nurul Ain; Manaf, Marina Abdul; Harith, Sakinah; Ishak, Wan Rosli Wan (Universiti Sains Malaysia, 2018)
Objective: The feasibility of developing reduced-fat muffins with avocado is investigated by preparing muffins with 25%, 50%, 75%, and 100% avocado puree as a fat (butter) replacer. Methodology: The resulting products were compared to the control muffin, which was made with 100% butter. Muffins were analyzed for nutritional content, fatty acid profiles, and sensory acceptability. Result: Muffins incorporated with avocado puree revealed a significant increase (p < 0.05) with respect to moisture, ash, and carbohydrate in comparison with the control sample. However, no significant changes (p > 0.05) were detected in all muffin formulations for protein and dietary fiber content. Both fat content and caloric value of muffins incorporated with avocado puree were significantly decreased (p < 0.05). The fatty acid profile showed that there was an increment in the monounsaturated fatty acids (MUFA) content by 16.51% at full-fat substitution. The sensory evaluation test demonstrated that muffins had acceptability at up to 50% substitution. Fat substitution at higher than 50% lead to undesirable flavor and aftertaste, which was significant (p < 0.05) to the panelists. Conclusion: The findings indicated the feasibility of avocado puree in fat-reduced muffin preparation with an optimal level of 50% avocado puree substitution.